2017
DOI: 10.22159/ijpps.2017v9i2.13793
|View full text |Cite
|
Sign up to set email alerts
|

Design and in Vitro Characterization of Mucoadhesive Buccal Patches of Duloxetine Hydrochloride

Abstract: Objective: Buccal mucosa is a potential site for the delivery of drugs to the systemic circulation, a drug administered through the buccal mucosa enters directly to the systemic circulation, thereby which bypass the drug from the first -pass hepatic metabolism and adverse gastrointestinal effect. Duloxetine hydrochloride (DLX HCL) is a selective serotonin and noradrenaline reuptake inhibitor (SSNRI). It is used in the treatment of depression, diabetic peripheral neuropathic pain and in moderate to severe stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In a previous study, Peddapalli et al. ( 2017 ) prepared DH buccal patches to improve the drug bioavailability by bypassing the hepatic metabolism and acid degradation in the stomach. This study concluded that DH can be delivered via the buccal route, however, the study did not support this claim by performing pharmacokinetic studies in human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Peddapalli et al. ( 2017 ) prepared DH buccal patches to improve the drug bioavailability by bypassing the hepatic metabolism and acid degradation in the stomach. This study concluded that DH can be delivered via the buccal route, however, the study did not support this claim by performing pharmacokinetic studies in human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…When the PVA-PVP layer is placed in contact with the mucosa, the drug compound migrates through the polymer and partitions across the interface of polymer/mucosa, which consequently migrates into the mucosa. The initial fast permeation may be attributed to the rapid diffusion of the drug to the surface of the film [16]. With time, swelling of polymer matrix occurred and varied the entanglement of polymeric pathways to control the drug diffusion from the matrix.…”
Section: In Vitro Permeationmentioning
confidence: 99%
“…Materials with hydrophobicity, low water permeability and drug impermeability properties such as melted wax [10], ethyl cellulose [1,4,11], and Eudragit RL100 [12] have been used as a backing membrane. A wide range of polymers such as hydroxypropyl methylcellulose, carbopol, poly (vinyl alcohol) (PVA), and poly (vinyl pyrrolidone) (PVP) [13][14][15][16][17] have been employed as a matrix and mucoadhesive layer in buccal patches. In order to improve the film properties, including film-forming ability, mechanical and mucoadhesive properties, a combination of hydrophilic polymers is generally used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buccal mucosa is a potential site for the delivery of drugs to the systemic circulation, a drug administered through the buccal mucosa enters directly the systemic circulation, thereby minimizing the firstpass hepatic metabolism and adverse gastrointestinal effect [6]. The oral mucosa, mainly the buccal site rather attractive for drug delivery [7], because the mucosa is relatively permeable with a rich blood supply, it is easily accessible, relatively immobile mucosa, suitable for administration of retentive dosage forms, termination of therapy at any time, comparatively less susceptibility to enzymatic activity, and useful for pediatric and geriatric patients. Hence, various mucoadhesive dosage forms were prepared for oral delivery, in the form of adhesive tablets [8][9][10][11][12][13], adhesive gels, buccal ointments [14,15], Bioadhesive Wafers [16], Bioadhesive lozenges [17], Bioadhesive Microparticles [18], and adhesive patches [19,20].…”
Section: Introductionmentioning
confidence: 99%